2006
DOI: 10.1167/iovs.05-0891
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Detection Is Facilitated by Luminance Modulation of the Global Flash Multifocal Electroretinogram

Abstract: The peripheral DC luminance-modulated response function is altered by the adaptive mechanism that is induced by the global flash; the reduction of the adaptive index may thus relate to an abnormal adaptive mechanism, presumably due to inner retinal damage. Glaucoma appears to produce large reductions of the adaptive index which correlate with field defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 24 publications
11
85
3
Order By: Relevance
“…Previous studies have shown that IC represents predominantly inner retinal function. [13][14][15] Based on this evidence, emmetropic children with subclinical decreased inner retinal function in the central region may be more likely to subsequently develop myopia.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that IC represents predominantly inner retinal function. [13][14][15] Based on this evidence, emmetropic children with subclinical decreased inner retinal function in the central region may be more likely to subsequently develop myopia.…”
Section: Discussionmentioning
confidence: 97%
“…In glaucoma, amplitudes of the peripheral DC were reduced at mid-luminance difference levels and therefore did not reach saturation level as soon. An adaptive index of the DC showed a good differentiation between healthy subjects and glaucoma patients with an area under the curve (AUC) of 0.986 (sensitivity: 93 %, specificity: 95 %) [13]. The total recording time needed to obtain this data was 6 9 8 min which does not seem feasible in the clinic.…”
Section: Introductionmentioning
confidence: 98%
“…The global flash paradigm consists of a periodic global flash interleaved with the pseudorandom binary m-sequence multifocal stimulation. This flash sequence produces two components, a direct component (DC) and an induced component (IC); the DC is analogous to a standard mfERG response and reflect certain light adaptation produced by the periodic global flashes [19], while the IC is the change in the response to the global flash produced by the prior local flash, and has been reported to be affected in glaucoma [20][21][22][23]. Naso-temporal response asymmetry across the retina is reported for the IC of the human global flash mfERG, which is a nonlinear response component predominantly from the inner retina [18].…”
Section: Introductionmentioning
confidence: 99%
“…To quantify retinal adaptation, our group derived an index from the DC induced by luminance-modulated global flash mfERG, which is calculated by subtracting the area under the line joining the responses from high (2.12 cd·s/m 2 ) to low (0.62 cd·s/m 2 ) luminance-difference from the area under the luminance-modulated response function fitted with a secondorder best-fit line of the DC responses, which indicates the dependence on the luminance-difference in the luminancemodulated response function [23]. This adaptive index was demonstrated to be sensitive to glaucomatous damage and correlated well with the localized visual field defect in individual patients.…”
Section: Introductionmentioning
confidence: 99%